Acquired salinity tolerance in rice: Plant growth dataset - Sriskantharajah, Karthika; Osumi, Shota; Chuamnakthong, Sumana; Nampei, Mami; Amas, Junrey C.; Gregorio, Glenn B.; Ueda, Akihiro (Elsevier, 2020)
This article describes the growth of 18 acclimatized and 11 non-acclimatized rice varieties grown in a hydroponic nutrient solution in a glasshouse. Four plants from each variety were grown under control conditions, salinity stress following control conditions (salinity), and salinity stress following acclimation (salinity/acclimation) conditions. Sampling was performed at the end of the salinity treatment (36 days of growth). Growth traits such as shoot and root biomass accumulation and lengths were measured for each variety, and the average was calculated using four replicates. This dataset may aid interested researchers in making comparisons with their data and further advance the research on the salinity acclimation process in rice.